Penegakkan Hukum dan Sanksinya Berdasarkan Peraturan Daerah Nomor 5 Tahun 2014 terhadap Upaya Perlindungan Hukum pada Anak Jalanan Beserta Hambatannya di Kota Semarang - Ajeng Ayu Rahmawati; Fitika Andraini; Dyah Listyarini (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The author's research was in writing a thesis entitled Law Enforcement and Sanctions Based on Regional Regulation Number 5 of 2014 on Legal Protection Efforts for Street Children and Their Obstacles in the City of Semarang. This research method involves field surveys, interviews, and qualitative data analysis. The data sources used will produce a description of what will later be described in the form of written or spoken sentences (interviews) by law enforcers who experience exploitation of street children in the city. Semarang, as well as supporting sources such as laws and regulations, books or other literacy. The results of this research highlight the complexity of the reality of street children's lives and offer deeper insight into the efforts that can be made to improve their welfare